Production of biodiesel from waste cooking oil and RBD palm oil using batch transesterification process - Siti Fatimah, Arifin (2009)
Waste Cooking Oil (WCO) has significant potential as the raw material or starting substance for biodiesel production. The objective of this research is to examine the performance of yield and purity of biodiesel from WCO as the starting material with different catalyst (NaOCH3) concentration and reaction time via single step batch transesterification process. It is also to investigate the extent to which the sodium methoxide (NaOCH3) as the catalyst and the effect of batch transesterification process on various parameters in production of biodiesel. The purity of methyl ester content in biodiesel is measured by Gas Chromatography. The exhaust emissions of biodiesel produced were evaluated by combustion test using Gas Combustion Unit. Results indicate that the higher conversion was obtained when RBD palm oil which is 98.2% yield and 97.5% purity instead of 96.8% yield and 94.7% purity in WCO used as the raw material. Biodiesel produced from WCO gives less exhaust emission of CO and CO2 compared to commercial diesel thus contributed to the reduction of greenhouse gas that effect the global warming.